The Expressionist Influence in Eugene O'Neill’s Plays - Kisselincheva, Ksenia (Sledva : NBU Journal of Humanities and Arts, 2020)
The main focus in this study is the unique individual reception of the Expressionism in some of Eugene O'Neill’s plays from the 1920s: "The Emperor Jones" (1920) and "The Hairy Ape" (1922). A strong source of influence is August Strindberg and his experiments at the Chamber Theater in Stockholm. This can be traced by pointing out common thematic and stylistic features in Strindberg's trilogy "The Road to Damascus" and O'Neill's "The Emperor Jones". Another major source of influence is the German Expressionist movement from the first quarter of the 20th century, especially some of the leading playwrights like Georg Kaiser and Ernst Toller. Yet another source of influence are the German Expressionistic films of R. Wiene, F. Lang and Murnau, which followed most of the principles of the avant-garde trend.